Proteomic Profiling of Astrocytic O-GlcNAc Transferase-Related Proteins in the Medial Prefrontal Cortex - Fan, Jun; Zhong, Qiu-Ling; Mo, Ran; Lu, Cheng-Lin; Ren, Jing; Mo, Jia-Wen; Guo, Fang; Wen, You-Lu; Cao, Xiong (Frontiers in Molecular Neuroscience, 2021)
The medial prefrontal cortex (mPFC), a key part of the brain networks that closely related to the regulation of behavioral, act as a key regulator in emotion, social cognition, decision making. Astrocytes are the majority cell types of glial cells, which play a significant role in a number of processes and establish a suitable environment for the functioning of neurons, including the brain energy metabolism. Astrocytes dysfunction in the mPFC has been implicated in various neuropsychiatric disorders. Glucose is a major energy source in the brain. In glucose metabolism, part of glucose is used to convert UDP-GlcNAc as a donor molecule for O-GlcNAcylation, which controlled by a group of enzymes, O-GlcNAc transferase enzyme (OGT) and O-GlcNAcase (OGA). However, the role of O-GlcNAcylation in astrocytes is almost completely unknown. Our research showed that astrocytic OGT could influence the expression of proteins in the mPFC. Most of these altered proteins participate in metabolic process, transferase activity, and biosynthetic process. GFAP, an astrocyte maker, was increased after OGT deletion. These results provide a framework for further study on the role of astrocytic OGT/O-GlcNAcylation in the mPFC.